RELATIONSHIP BETWEEN CARDIAC ARRHYTHMIAS AND THE PREVALENCE OF PULMONARY THROMBOEMBOLISM: A LITERATURE REVIEW (CIPEEX, 2025)
Cardiac arrhythmias, such as atrial fibrillation, are conditions characterized by abnormal heart rhythms that can lead to serious complications, including thromboembolism. Pulmonary embolism, an acute obstruction of the pulmonary arteries typically caused by thrombi, is associated with high morbidity and mortality. Recent studies suggest a significant relationship between cardiac arrhythmias and the prevalence of pulmonary embolism, with implications for diagnosis, treatment, and prognosis. Understanding this interaction is crucial for developing prevention and clinical management strategies. This summary aims to analyze the relationship between cardiac arrhythmias and the prevalence of pulmonary embolism, evaluating their frequency, risk factors, and clinical implications based on recent evidence. Studies were collected from databases such as Scielo and PubMed, including multicenter analyses, systematic reviews, and guidelines, covering the period up to August 2025. The analysis included associations between atrial fibrillation and pulmonary embolism, clinical outcomes, and anticoagulation strategies. Studies with irrelevant populations, inadequate methodology, insufficient data, or paid access were excluded. Eight studies from 2015 to 2024 were selected. Atrial fibrillation, whether pre-existing or newly diagnosed, is significantly associated with worse outcomes in patients with pulmonary embolism, including higher mortality and thromboembolic complications. A multicenter study involving over 45,000 arrhythmia ablation procedures identified an increased risk of post-procedure pulmonary arterial embolism, with incidence rates ranging from 0.1% to 0.5%. Newly identified atrial fibrillation in patients with pulmonary embolism was associated with greater disease severity and the need for intensive interventions. Additionally, anticoagulation for the prevention of venous thromboembolism and stroke in patients with atrial fibrillation and comorbidities, such as cirrhosis, is recommended but requires individualized management due to bleeding risks. The relationship between cardiac arrhythmias, particularly atrial fibrillation, and pulmonary embolism is clinically significant, with atrial fibrillation increasing the severity and risk of complications in patients with pulmonary embolism. Procedures such as catheter ablation elevate the risk of pulmonary embolism, underscoring the need for rigorous monitoring and antithrombotic prophylaxis. Anticoagulation is essential but must be tailored, especially in high-risk populations. Future studies should focus on strategies to reduce the incidence of pulmonary embolism in patients with arrhythmias and optimize clinical management to improve outcomes.
Keywords: Arrhythmias; Cardiac; Pulmonary Embolism; Cardiovascular Health